Phytohormone and Light Regulation of Chlorophyll Degradation - Zhu, Xiaoyu; Chen, Junyi; Qiu, Kai; Kuai, Benke (Frontiers in Plant Science, 2017)
Degreening, due to the net loss of chlorophyll (Chl), is the most prominent symptom during the processes of leaf senescence, fruit ripening, and seed maturation. Over the last decade or so, extensive identifications of Chl catabolic genes (CCGs) have led to the revelation of the biochemical pathway of Chl degradation. As such, exploration of the regulatory mechanism of the degreening process is greatly facilitated. During the past few years, substantial progress has been made in elucidating the regulation of Chl degradation, particularly via the mediation of major phytohormones’ signaling. Intriguingly, ethylene and abscisic acid’s signaling have been demonstrated to interweave with light signaling in mediating the regulation of Chl degradation. In this review, we briefly summarize this progress, with an effort on providing a framework for further investigation of multifaceted and hierarchical regulations of Chl degradation.